EFFECTS OF KNOWLEDGE-BASED INFERENCES TRAINING ON PRIMARY GRADE CHILDREN WITH READING DISABILITIES - VIOREL MIH (Studia Universitatis Babes-Bolyai, 2011)
ABSTRACT. Student development and use of effective reading comprehension strategies is one of the most important goals for content area reading instruction. Therefore, strategy instruction should be part of the total school curriculum, and students should be taught to apply strategies in various content area classes. Students with reading disabilities in primary school grades need assistance in content reading to integrate new information with their prior knowledge, to obtain important information from the text, and to remember what they have read. Thus, content area reading instruction is an important component of curricula and includes strategy instruction in comprehension skills. The purpose of this article is to assess the impact of introducing inference training to less skilled comprehenders. Children 3-ed grades, classified as skilled or less skilled comprehenders, were instructed on how to make inferences from and generate questions about a text over a period of seven sessions. Comparison groups of control and experimental were trained in standard comprehension strategies. The experimental group showed a significantly greater improvement in inference generation than the control group. It is concluded that the value of explicitly teaching children inferential skills is that the enjoyment of the task of reading is enhanced and is therefore more likely to be undertaken readily, even by pupils who may have initially found reading difficult.